Touching the (almost) untouchable: a minimally invasive workflow for microbiological and biomolecular analyses of cultural heritage objects - Flocco, Cecilia G.; Methner, Anika; Burkart, Franziska; Geppert, Alicia; Overmann, Jörg (Frontiers in Microbiology, 2023)
Microbiological and biomolecular approaches to cultural heritage research have expanded the established research horizon -from the prevalent focus on the cultural object's' conservation and human health protection to the relatively recent applications to provenance inquiry and assessment of environmental impacts on heritage objects in a global context of a changing climate. Standard microbiology and molecular biology methods were developed for other materials, specimens, disciplines and contexts. Although they could, in principle, be applied to cultural heritage research.,However, given certain characteristics common to several heritage objects -such as uniqueness, fragility, high value and restricted access, demand tailored approaches are required. In addition, samples of heritage objects often may yield low microbial biomass, rendering them highly susceptible to cross-contamination. Therefore, dedicated methodology that addressesaddressing these material limitations and operational hurdles along all procedural steps are needed. Here we review the main challenges and propose a step-by-step standardized workflow to analyse study the microbiome of cultural heritage objects, illustrated by the exploration of bacterial taxa. The methodology was developed targeting the challenging side of the spectrum of cultural heritage objects, such as the delicate written record, while retaining modularity and flexibility to adapt and/or upscale the proposed workflowit to heritage artefacts of a more robust constitution nature or larger dimensions. We hope this tailored review and workflow will facilitate the interdisciplinary inquiry and interactions among the cultural heritage research community.